2011
DOI: 10.1016/j.yexmp.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of SNAP-treated adipose tissue-derived stem cells improves cardiac function and induces neovascularization after myocardium infarct in rats

Abstract: Stem cell therapy has been considered a promise for damaged myocardial tissue. We have previously shown that S-nitroso-N-acetyl-D,L-penicillamine (SNAP) increases the expression of several muscular markers and VEGF in mesenchymal stem cells, indicating that transplantation of SNAP-treated cells could provide better functional outcomes. Here, we transplanted SNAP-treated adipose tissue-derived stem cells (ADSCs) in rat infarcted myocardium. After 30days, we observed a significant improvement of the ejection fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Pharmacological treatment of ADSCs, with rosuvastatin [51], ghrelin [52], T0901317 [53], exendin-4 [54], S-nitroso- N -acetyl- d,l -penicillamine (SNAP) [55], and NapFF-NO (FFGGG, and b-galactose caged nitric oxide) [56] etc., has increased the efficacy of ADSCs in promoting retention and the paracrine function of implanted cells. Rosuvastatin was used to promote the survival of ADSCs after transplantation into infarcted hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment of ADSCs, with rosuvastatin [51], ghrelin [52], T0901317 [53], exendin-4 [54], S-nitroso- N -acetyl- d,l -penicillamine (SNAP) [55], and NapFF-NO (FFGGG, and b-galactose caged nitric oxide) [56] etc., has increased the efficacy of ADSCs in promoting retention and the paracrine function of implanted cells. Rosuvastatin was used to promote the survival of ADSCs after transplantation into infarcted hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups have studied its vasodilation effects [ 37 ] and regulation of the platelet aggregation in the past [ 38 ]. Meanwhile, NO molecules can also promote the expression of pro-angiogenic cytokines, favorable for angiogenesis [ 39 ]. Therefore, modulation in level of NO by cardiomyocytes in response to a vascular implant is of great interest to the engineers.…”
Section: Discussionmentioning
confidence: 99%
“…Yao and his group cultured adipose-derived MSCs in a hydrogel that can release NO molecule continuously and transplanted the hydrogel into murine myocardial infarction (MI) models, which achieved positive therapeutic effects (Yao et al, 2015). It has been widely confirmed that the protective effect of MSCs on MI is mainly achieved through the pro-angiogenic cytokines it secreted (Berardi et al, 2011). Similarly, Yao and co-workers discovered that NO hydrogel remarkably enhanced the paracrine and the VEGF secretion of MSCs.…”
Section: Small Bioactive Moleculesmentioning
confidence: 99%